Tu sais, mon vieux Jean-Pierre : Essays on the Archaeology and History of New France and Canadian Culture in Honour of Jean-Pierre Chrestien - Chrestien, Jean-Pierre, 1949-2008; Willis, John, 1954- (Book collections on Project MUSE., 2017)
"Tu sais mon vieux Jean-Pierre consists of a series of essays on the archaeology and history of New France. It is inspired by the work of archaeologist Jean-Pierre Chrestien (1949-2007), who worked hand-in-glove with a generation of researchers in helping to unearth unexpected and always interesting aspects of New France. Contributions focus first upon the door to New France in the Gulf of St. Lawrence, Newfoundland and Acadia. A second set of essays move further up the St. Lawrence and into the heartland of the continent. The final section examines certain aspects of Canadian culture: popular art, religion and communication. The essays are tied together by a curiosity for material culture, a careful regard for detail and nuance that forms the grain of New France studies, and sensitivity to the overall context that is part and parcel of how history proceeds on the local or regional scale. The essays offer a different perspective on subjects that hopefully the larger community will find stimulating."--